Kontruksi Pembuktian Teorema pada Matakuliah Geometri Euclid Melalui Aktivitas Think Pair Share - Zaini .; Mufidah . (Jurnal Inspirasi Pendidikan, 2014)
Proofing of the theorem requires logical thinking process and informatics analyses on the data used to deriving a conclusion. In these cases, each individual has different Level of Actual Development (LAD), Level of Potential Development (LPD) and Zone of Proximal Development (ZPD). Vygotsky said “all higher psychological processes are originally social processes, share between people, particularly between children and adult“. The aim of this research is to describe theorem proof construction using think pair share activity. The result show, on the think step, the level of potential development in student can proof theorems at 1, 4, 5, 6, 7, 14, 15, 16, and 17. Think code B1, B2, B5, B6, B7, B8, and B10 in second theorem. Think code C2, C3, C4, C5, and C6 in third theorem. Think code H3 in eighth theorem. Think code K6 (as conclusion) in tenth theorem. Think code K2, K4, K5, and K6 in 11th theorem. Think code M7 in 12th theorem, the conclusion at 13th theorem. Think code T8, T9, and T10 in 18th theorem achieved yet. In pair step LPD and ZPD with scaffolding can help student to achieve think code theorem. Keywords: construction, theorem, think pair share